Compadrio e família em zona de fronteira agrícola: as redes sociais da elite escravista, freguesia de Guarapiranga (c1760-c1850) - Mateus Rezende de Andrade (2014)
This work aims to analyze the mutual interference between marriage and godparentage among members of slaveholding elite. It is believed that these two relational practices offer important keys to understanding social hierarchies , social and spatial mobility and social embedded, besides giving subsidies to know the mechanisms of maintenance of social prestige and power. Was used in the research conducted, information contained in population censuses, postmortem inventories and parish records. Through specific techniques of historical demography, the space under study was known as the population composition . Nominally crossing data of cartorial documentation and parish records were created social networks which revealed some of the relational patterns of this elite. As results, were noted social relationships the involved within and outside members from families of these slaveholding elite, which were consequences of distinct strategies and thus it has to be examined separately. It was also observed that through marriages with important families entrenched in the region since the beginning of the occupation process, individuals from other regions aspired social and economic ascension through insertion in the main relational circles of Piranga. Finally, have been noted significant differences in intergenerational practice of godparentage, which demonstrates the importance in analyzing this practice jointly the life cycle.